Investigating barriers to tax payment in the informal sector of Ghana: a case study in Nkwanta north area. - Atitsogbui Ameko Felix (knust, 2025)
A thesis submitted to the Department of Accounting and Finance, School of Business, College of Humanities and Social Sciences in partial fulfilment of the requirement for the award of Master of Science Degree in Accounting and Finance